Analysis of Dissolution of Salicylamide from Carrageenan Based Hard-Shell Capsules: A Study of the Drug-Matrix Interaction - Muhammad Al Rizqi Dharma Fauzi; Esti Hendradi; Pratiwi Pudjiastuti; Riyanto Teguh Widodo (Universitas Gadjah Mada, 2021)
In drug release kinetics, the drug-matrix interaction is one of the important mechanisms to be dictated. Unfortunately, there is still minimum information discussing the effect of interaction between a drug and its matrix to the release profile of the drug. Therefore, there is an urgent need to conduct research related to the study of drug-matrix interaction. This paper reports the preparation of a drug delivery system (DDS) in the form of hard-shell capsules containing salicylamide (SCA) and analyses its drug-matrix interaction via dissolution test at different pH media and various release kinetics models. The matrix of hard-shell capsules was prepared from κ-carrageenan (CRG), crosslinked with maltodextrin (MD), and plasticized by sorbitol (SOR). The chemical properties of SCA were compared with paracetamol (PCT) using computational analysis to help to depict its drug-matrix interaction. The statistical analyses showed that SCA and PCT at pH 1.2, 4.5, and 6.8 had all different release profiles. Based on the goodness of fit evaluation, the diffusion mechanism of SCA at pH 1.2 and 4.5 could be best described by the Peppas-Sahlin model while the zeroth-order model fitted the dissolution profile at pH 6.8. In summary, it was proven that a different drug-matrix interaction produced a different dissolution profile.